The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1975
DOI: 10.1104/pp.55.5.845
|View full text |Cite
|
Sign up to set email alerts
|

14C2H4: Its Purification for Biological Studies

Abstract: A gas chromatographic technique is described for obtaining ultra high purity 14(GH for use in biological studies. l4CHL purchased from commercial sources contained readily detectable impurities including radioactive acetylene. Following purification on two different columns, no impurities were detected by high sensitivity gas chromatographic analysis. However, shortly thereafter impurities were detected as a result of radiation decomposition. Trapping and immediately regenerating ultra high purity 14C24 from d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
9
0

Year Published

1975
1975
1989
1989

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 8 publications
0
9
0
Order By: Relevance
“…The use of '4CM,4 to study its possible incorporation and metabolism by plants is not straightforward as demonstrated by the number and kind of problems encountered and alluded to above and in a previous report (5). The difficulty in working with 14CM,4 is not only attributable to its instability (5,18) but also to the relatively small amounts of radioactivity which are incorporated and converted to "4CO2 at physiological concentrations of 14CH4.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The use of '4CM,4 to study its possible incorporation and metabolism by plants is not straightforward as demonstrated by the number and kind of problems encountered and alluded to above and in a previous report (5). The difficulty in working with 14CM,4 is not only attributable to its instability (5,18) but also to the relatively small amounts of radioactivity which are incorporated and converted to "4CO2 at physiological concentrations of 14CH4.…”
Section: Discussionmentioning
confidence: 99%
“…The difficulty in working with 14CM,4 is not only attributable to its instability (5,18) but also to the relatively small amounts of radioactivity which are incorporated and converted to "4CO2 at physiological concentrations of 14CH4. As the level of radioactivity decreases the likelihood increases that the label incorporated and converted to "4CO2 is an impurity rather than '4C2H4.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Prior to placing the abscission zone or petiole segments into the incubation flasks, sufficient distilled H20 was added to the flask to cover the bottom (4 ml), and 1 ml of 1.5 N NaOH was placed in the small, side well container to trap "4CO2. The flasks were sealed, and enough purified 14C2H4 (7) injected to yield a final concentration of 20 Al/ 1 which was subsequently verified by GC analysis. The flasks were incubated on a shaker for 5.5 h in the dark at 22 C.…”
mentioning
confidence: 99%